A protocol for random multiple access of packets with mixed priorities in wireless networks. - Papantoni-Kazakos, T.
Random multiple access (RMA) protocols comprise an important class for the accessing/signaling stage in multimedia ATM wireless networks. Within the RMA class, the ALOHA algorithm is most widely used at this point in time, while, as is well known, the latter algorithm becomes unstable, as the user population increases. In this paper, we consider the part-and-try algorithm, instead, for a system with different priorities. Based on this algorithm, we construct a mixed priority protocol whose total throughput-for all priorities combined-equals 0.487. In the special and important for ATM case of two, low, and high priorities, with respective Poisson intensities λL and λH. We also present an analytical methodology which allows the computation of the average packet delays as functions of the rates λL and λH
Keywords: ALOHA algorithm; Poisson intensities; Average packet delays; Mixed priority protocol; Multimedia ATM wireless networks; Part-and-try algorithm; Random multiple access protocol; Signaling stage; Throughput